Mobilisation of reserves during germination of seeds of Tabebuia roseo-alba (Bignoniaceae) - Abbade, Leticia Caravita [UNESP]; Takaki, Massanori [UNESP] (Ista-int Seed Testing Assoc, 2012)
Tabebuia roseo-alba is a native Brazilian tree species with wide occurrence, particularly in semi-deciduous forest. The tree has lush flowering and is used in landscaping, arboriculture and for reforestation of dry and rocky soils. Its seeds are small, lightweight and winged, and are wind-dispersed. The objective of this study was to investigate the biochemical changes in T. roseo-alba seeds during germination. We determined the content of starch, structural polysaccharides, lipid and soluble protein, and analysed the proteins by SDS-PAGE. There was a rapid consumption of starch, structural polysaccharides, lipids and proteins during germination of T. roseo-alba seeds. The rapid mobilisation of protein during germination, was accompanied by the synthesis of high molecular mass proteins and degradation of low molecular mass proteins.